The effect of molecular weight on the surface and permeation of poly(L-lactic acid)-poly(ethylene glycol) membrane with activated carbon filler - Afifah Muhamad Sidik; Rizafizah Othaman; Farah Hannan Anuar (Penerbit Universiti Kebangsaan Malaysia, 2018)
The use of biodegradable material in membrane technology will be a great solution in reducing non-biodegradable waste in the landfill. Membranes can often be useful as the recycle stream can usually be much cleaner than with other techniques. This article describes the preparation of poly(l-lactic acid)-poly(ethylene glycol) (PLLA-PEG) free standing flat sheet membranes with the presence of 5 wt. % activated carbon filler. PLLA-PEG crosslinked copolymer was synthesized using PLLA with different molecular weight PEG prepolymers i.e. 4000, 6000 and 10000 g/mol; and excess hexamethylene diisocyanate to form urethane linkages between the polymers. The reaction was carried out in a dichloromethane/tetrahydrofuran dual-solvents system. The PLLA-PEG/AC membranes in the weight ratio of 7:3:0.5 were then fabricated using solution casting and phase inversion techniques. The performance of the membranes was evaluated in terms of permeation water flux (PWF), palm oil mill effluent (POME) permeation, flux decline and contact angle. It was found that membrane containing 10000 g/mol PEG has the highest total mean in PWF, POME flux and hydraulic permeability with values of 100.9 L/m2.h, 51.45 L/m2.h and 64.9º;62.9º, respectively, due to high porosity. All of the membranes were more stable towards the flux decline of POME compared to water. At the same time, addition of AC to the copolymer considerably enhances the texture and porosity of the fabricated membranes.